A Comparison of the NZTM and FPS Models of the New Zealand Economy - Kam Leong Szeto; Paul Gardiner; Richard Gray; David Hargreaves (New Zealand Government, The Treasury, 2003)
This paper investigates and compares the dynamic properties of the New Zealand Treasury model (NZTM) and the current version of the Reserve Bank's Forecasting and Policy System model (FPS). The main use of both two models is to produce macroeconomic forecasts. The NZTM model produces forecasts that are used as an input into the final forecast numbers presented in the Economic and Fiscal Updates. The FPS model is used to produce the published forecasts in the Reserve Bank's quarterly Monetary Policy Statement. Both models contain a number of judgements around the structure of the economy, the key shocks that impact on the economy, and how the economy evolves in response to these shocks. The paper concludes that one of the main differences between the two models occurs in the impact of a world price shock on the real exchange rate and subsequently on exports and imports. Another key difference is the mechanism through which the net foreign asset position returns towards equilibrium. In FPS, the external balance is partly attained by forward-looking consumers who adjust spending to reach desired wealth positions. In contrast, the real exchange rate is the key mechanism in NZTM for re-establishing equilibrium.
Keywords: E10; E17; E63; 330; New Zealand; NZTM; FPS; Macroeconomic forecasts; Net foreign asset position; forwarding-looking consumers; Real exchange rate